PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL BERBASIS KOMPETENSI UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN - Hartoyo FT (Jurnal Kependidikan, 2009)
The aim of this study was to improve the learning effectiveness of both learning process quality and standard competency achievement in the application of the competency-based contextual learning model in the Cooling Technique and Air Management class. The study was conducted in Elekctrical Department of Engineering Faculty of Yogyakarta State University. The study was classroom action research involving several cycles. Each cycle consisted of planning, action, observation, and reflection. The research subjects were 13 D3 students who took the subject of the Cooling Technique and Air Management during the odd semester in the academic year of 2008/2009. Data were gathered using questionnaires, observation, tests, and tasks or quizzes. Data analysis was descriptive using percentages. The results showed that the use of the competency-based contextual learning model on the subject of Cooling Technique and Air Management was able to improve learning effectiveness of both the process and output of learning. Key words: contextual learning, competency-based learning, standard competencies, learning process, learning output